1988
DOI: 10.1002/hep.1840080116
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic encephalopathy and orotic aciduria associated with hepatocellular carcinoma in a noncirrhotic liver

Abstract: A 40-yr-old man presented with encephalopathy and was found to have hepatocellular carcinoma without cirrhosis. A large vascular hepatic mass was defined by CT scan and angiography; laparoscopy with biopsy confirmed the absence of chronic liver disease. A definitive tissue diagnosis of hepatocellular carcinoma was made at laparotomy; the tumor was unresectable. Peripheral arterial and selective portal and hepatic venous ammonia levels were high, and this finding suggested that the encephalopathy was nitrogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 7 publications
1
12
0
1
Order By: Relevance
“…Although initial metabolic investigations suggested inherited OTC deficiency, this was not confirmed by DNA analysis. Similar cases have been reported in the literature of patients with FLC (Jeffers et al 1988;Sethi et al 2009) presenting with hyperammonaemic encephalopathy, in some cases related to chemotherapy (Chan et al 2008;Winter et al 1997). A previous study on rats has shown an inverse relationship between ornithine carbamyl transferase activity and the rate of growth of hepatoma (Weber et al 1972).…”
Section: Discussionsupporting
confidence: 73%
“…Although initial metabolic investigations suggested inherited OTC deficiency, this was not confirmed by DNA analysis. Similar cases have been reported in the literature of patients with FLC (Jeffers et al 1988;Sethi et al 2009) presenting with hyperammonaemic encephalopathy, in some cases related to chemotherapy (Chan et al 2008;Winter et al 1997). A previous study on rats has shown an inverse relationship between ornithine carbamyl transferase activity and the rate of growth of hepatoma (Weber et al 1972).…”
Section: Discussionsupporting
confidence: 73%
“…A recent study in rats showed that OAT2 is responsible for the uptake of orotic acid [24], which reportedly promotes liver carcinogenesis [25,26]. In the clinical setting, orotic aciduria was also observed in HCC patients without liver cirrhosis [27]. Moreover, a previous study using gene-set enrichment analysis revealed that SLC22A7 expression is significantly correlated with mitochondrial oxidoreductase activity and fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…OTC inhibition can be induced by carcinogens and/or carcinogenesis (McLean, 1964;Jeffers, 1988;Riordan, 1997) although the mechanism is unknown. Of possible relevance to that mechanism is that OTC is known to be negatively regulated by acetylation (Weber, 1972), and deacetylated (activated) by Sirt3 (Xu, 2011).…”
Section: Alternate Pyrimidine Biosynthesis Paths Of Clinical Relevancementioning
confidence: 99%